Targeting PCSK9 for therapeutic gains: Have we addressed all the concerns?. (May 2016) - Banerjee, Yajnavalka; Santos, Raul D.; Al-Rasadi, Khalid; Rizzo, Manfredi
Abstract: Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) regulates the expression of low-density lipoprotein (LDL)-receptors, through reducing their recycling by binding to the receptor along with LDL and targeting it for lysosomal destruction. PCSK9 also enhances the degradation of very-low-density-lipoprotein receptor (VLDLR) and lipoprotein receptor-related protein 1 (LRP-1) in a LDL-receptor independent manner. This role in lipid homeostasis presents PCSK9 as an attractive target for the therapeutic management of familial hypercholesterolemia as well as other refractory dyslipidaemias. However, PCSK9 mediates multifarious functions independent of its role in lipid homeostasis, which can be grouped under "pleiotropic functions" of the protein. This includes PCSK9's role in: trafficking of epithelial sodium channel; hepatic regeneration; pancreatic integrity and glucose homeostasis; antiviral activity; antimalarial activity; regulation of different cell signalling pathways; cortical neural differentiation; neuronal apoptosis and Alzheimer's disease. The question that needs to be investigated in depth is "How will the pleotropic functions of PCSK9, be affected by the therapeutic intervention of the protease's LDL-receptor lowering activity?" In this review, we appraise the different lipid lowering strategies targeting PCSK9 in light of the protein's different pleiotropic functions. Additionally, we delineate the key areas that require further examination, to ensure the long-term safety of the above lipid-lowering strategies. Highlights: Several lipid lowering strategies targeting PCSK9 have been designed to manage hypercholesterolemia. PCSK9 mediates several physiological effects, which are independent of cholesterol homeostasis. Long-term PCSK9 inhibition may detrimentally affect these physiological effects and therefore should be carefully evaluated.